2022
DOI: 10.3389/fpsyg.2022.1028559
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and mental health: A systematic review of international medical student surveys

Abstract: BackgroundThe medical school curriculum has imposed psychological stressors on students worldwide, some of which may induce feelings of increased depression and anxiety. Meanwhile, the COVID-19 pandemic has exacerbated the feelings of stress, depression, and anxiety that a portion of medical students experience in their daily life. The aim of this systematic review is to gather concrete data from medical schools around the globe, and further evaluate how the COVID-19 pandemic has impacted medical students’ men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
1
13
0
2
Order By: Relevance
“…Fear of contracting the virus is high among college/university students more generally, irrespective of their subject discipline [61,62]. Our findings align with other studies that identified mental health impacts of the COVID-19 pandemic in the general population [1][2][3][4], healthcare professional [5][6][7][8] and healthcare trainee samples [10][11][12][13][14][15][16]. For some, the negative impacts of the pandemic on mental wellbeing were mitigated by environmental factors (e.g., good weather lifting mood), social support (e.g., from family members at home), or personality traits (e.g., those who reported introversion traits perceived reduced social contact to be less problematic).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Fear of contracting the virus is high among college/university students more generally, irrespective of their subject discipline [61,62]. Our findings align with other studies that identified mental health impacts of the COVID-19 pandemic in the general population [1][2][3][4], healthcare professional [5][6][7][8] and healthcare trainee samples [10][11][12][13][14][15][16]. For some, the negative impacts of the pandemic on mental wellbeing were mitigated by environmental factors (e.g., good weather lifting mood), social support (e.g., from family members at home), or personality traits (e.g., those who reported introversion traits perceived reduced social contact to be less problematic).…”
Section: Discussionsupporting
confidence: 88%
“…As the future healthcare workforce, trainees are capable and willing to be involved in global health emergencies [9], although the mental health of healthcare trainees has also been impacted during the COVID-19 pandemic [10][11][12][13][14][15][16]. Systematic reviews and metaanalyses found that student nurses reported suffering from fear, stress, anxiety, depression, and sleep disturbance [10,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outros fatores de risco importantes incluíram problemas econômicos, doença mental ou física pré-existente e infecção ou exposição à COVID-19, o que foi consistente com estudos em outras populações. Outras entrevistas qualitativas nesses estudantes de alto risco são necessárias para determinar como esses fatores impactaram a saúde mental dos estudantes de medicina (PAZ et al, 2022).…”
Section: Resultsunclassified
“…As in other countries [ 7 ], medical students in Japan have experienced psychiatric stress due to changes in the educational environment [ 8 , 9 ]. In a questionnaire survey conducted on medical students regarding students’ subjective psychological distress, it was found that students who expressed concerns about the rapid shift toward online education and anxiety about basic life security were more likely to be depressed and anxious after the surge in COVID-19 cases in Japan (April 2020) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%